Mediating Impact of Information Sharing on Information Quality and SCM Performance in SMEs - Eva Sundari; Awliya Afwa; Dani Pratama (Universitas Muhammadiyah Yogyakarta, 2024)
This research aims to examine and analyze the influence of information quality on Supply Chain Management (SCM) performance among Small and Medium-sized Enterprises (SMEs) in Pekanbaru City, utilizing information sharing as a mediator. The study employed institutional theory to elucidate the interactions between the variables, explaining how external factors such as social and cultural norms influence information-sharing practices among business actors and the role of legitimacy in promoting these practices. Focusing on SMEs that have implemented systems in their business management, the research utilized the Krejcie and Morgan table for sampling, engaging 177 SMEs willing to participate. Data analysis was conducted using the Partial Least Square (PLS) method through SEM-PLS software. The findings indicated that information quality significantly influenced SCM performance directly and influenced information-sharing practices. Importantly, the study revealed that Information Quality indirectly affected SCM performance through information sharing, which acts as a mediating variable. This research offers practical benefits to SME owners in Pekanbaru by enhancing SCM performance through improved information quality. It contributes academically as a reference to the impact of information quality on SCM with information sharing as a mediator.